A STUDY OF TEACHING ENGLISH SPEAKING SKILL THROUGH ONLINE LEARNING IN SMP UNGGULAN NU MOJOAGUNG - Nur Habibah; Maskhurin Fajarina (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2021)
This research was carried out when Coronavirus Disease-19 (COVID-19) pandemic occurred in various countries. This virus attacks the respiratory system and spreads very quickly to various parts of the country, one of which is Indonesia. The spread of the virus has forced the government to issue several policies aimed at breaking the ropes of the spread of the virus. One of the policies issued is to conduct online learning. This study answered three research problems, namely how to prepare, process, and results of teaching English speaking skills through online learning. This study used a descriptive qualitative method by conducting interviews. The results of this research indicated that teaching English in speaking skill through online learning is less optimal than face-to-face speaking learning. The teacher used WhatsApp as a media and take advantage of its features as a method of learning. Those media and methods are very effective compared to other methods and media. The teacher conducted learning by recording sound about the explanation of material. The researcher concluded that teaching English in speaking skills through online learning was not optimal. WhatsApp is an effective application used as a medium and method in teaching English in speaking skills through online learning.